Consciousness Without Attention - JENNINGS, CAROLYN DICEY (Journal of the American Philosophical Association, 2015)
This paper explores whether consciousness can exist without attention. This is a hot topic in philosophy of mind and cognitive science due to the popularity of theories that hold attention to be necessary for consciousness. The discovery of a form of consciousness that exists without the influence of attention would require a change in the way that many global workspace theorists, for example, understand the role and function of consciousness. Against this understanding, at least three forms of consciousness have been argued to exist without attention: perceptual gist, imagistic consciousness, and phenomenal consciousness. After first arguing that the evidence is inconclusive on the question of whether these forms of consciousness exist without attention, I here present a fourth form of consciousness that is likely to be more successful: conscious entrainment. I argue that conscious entrainment is a form of consciousness associated with skilled behavior in which attention is sometimes absent.